Functional constipation in children: challenges and solutions - Levy EI; Lemmens R; Vandenplas Y; Devreker T (Dove Medical Press, 2017)
Elvira Ingrid Levy,* Roel Lemmens,* Yvan Vandenplas, Thierry Devreker Kidz Health Castle, UZ Brussel, Vrije Universiteit Brussel, Brussels, Belgium *These authors contributed equally to this work Abstract: This review intends to update what is known about and what is still a challenge in functional constipation (FC) in children regarding epidemiology, pathophysiology, diagnosis, and management. Although FC is a common childhood problem, its global burden remains unknown as data from parts of the world are missing. Another problem is that there is a large variation in prevalence due to differences in study methods and defining age groups. The pathophysiology of FC remains unclear to date but is probably multifactorial. Withholding behavior is likely to be the most important factor in toddlers and young children. Genetics may also play a role since many patients have positive family history, but mutations in genes associated with FC have not been found. Over the past years, different diagnostic criteria for FC in infants and children have been proposed. This year, Rome IV criteria have been released. Compared to Rome III, it eliminates two diagnostic criteria in children under the age of 4 who still wear diapers. Physical examination and taking a thorough medical history are recommended, but other investigations such as abdominal radiography, transabdominal recto-ultrasonography, colonic transit time, rectal biopsies, and colon manometry are not routinely recommended. Regarding treatment, guidelines recommend disimpaction and maintenance therapy with polyethylene glycol (PEG) with or without electrolytes. But experience shows that acceptability, adherence, and tolerance to PEG are still a challenge. Counseling of parents and children about causes of FC is often neglected. Recent studies suggest that behavior therapy added to laxative therapy improves the relief of symptoms. Further homogeneous studies, better-defined outcomes, and studies conducted in primary care are needed. Keywords: functional constipation, children, epidemiology, pathophysiology, diagnostics, treatment, recurrent abdominal pain